Characteristics and accumulation model of the late Quaternary shallow biogenic gas in the modern Changjiang delta area, eastern China - Xia Zhang (KeAi Communications Co., Ltd., 2017)
Abstract The Changjiang (Yangtze) is one of the largest rivers in the world. It formed a huge incised valley at its mouth during the Last Glacial Maximum; the incised-valley fill, approximately 80–110 m thick, supplies an important foundation for the generation of shallow biogenic-gas reservoirs. Two cores and 13 cone penetration tests were used to elaborate the characteristics, formation mechanism, and distribution of the shallow biogenic-gas reservoirs in the study area. The natural gas is mainly composed of CH4 (generally >95%) with a δ13CCH4 and δ13CCO2 of −75.8 to −67.7‰ and −34.5 to −6.6‰, respectively, and a δDCH4 of −215 to −185‰, indicating a biogenic origin by the carbon dioxide reduction pathway. Commercial biogenic gas occurs primarily in the sand bodies of fluvial-channel, floodplain, and paleo-estuary facies with a burial depth of 50–80 m. Gas sources as well as cap beds are gray to yellowish-gray mud of floodplain, paleo-estuary, and offshore shallow marine facies. The organic matter in gas sources is dominated by immature type III kerogen (gas prone). The difference in permeability (about 4–6 orders of magnitude) between cap beds and reservoirs makes the cap beds effectively prevent the upward escape of gas in the reservoirs. This formation mechanism is consistent with that for the shallow biogenic gas in the late Quaternary Qiantang River incised valley to the south. Therefore, this study should provide further insight into understanding the formation and distribution of shallow biogenic gas in other similar postglacial incised-valley systems.